Semiconducting Polymer Nanobioconjugates for Targeted Photothermal Activation of Neurons - Lyu, Yan (2017)
Optogenetics provides powerful means for precise control of neuronal activity; however, the requirement of transgenesis and the incapability to extend the neuron excitation window into the deep-tissue-penetrating near-infrared (NIR) region partially limit its application. We herein report a potential alternative approach to optogenetics using semiconducting polymer nanobioconjugates (SPNsbc) as the photothermal nanomodulator to control the thermosensitive ion channels in neurons. SPNsbc are designed to efficiently absorb the NIR light at 808 nm and have a photothermal conversion efficiency higher than that of gold nanorods. By virtue of the fast heating capability in conjunction with the precise targeting to the thermosensitive ion channel, SPNsbc can specifically and rapidly activate the intracellular Ca2+ influx of neuronal cells in a reversible and safe manner. Our study provides an organic nanoparticle based strategy that eliminates the need for genetic transfection to remotely regulate cellular machinery.